Carcharhinus falciformis - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Carcharhinus falciformis (Müller & Henle, 1839). Silky Shark . To about 3.5 m (11.5 ft) TL (Weigmann 2016). Circumglobal; western Pacific Ocean at least as far northward as Ryukyu Islands (Yoshino and Aonuma in Nakabo 2002); Lagunas Ojo de Liebre-Guerrero Negro, central Baja California (Galván-Magaña et al. 2000) to northern Chile (Grove and Lavenberg 1997), including Gulf of California (Compagno et al. in Fischer et al. 1995), and Islas Galápagos (Grove and Lavenberg 1997). Depth: surface to 500 m (1,640 ft) or more (min.: Ebert et al. 2013; max.: Compagno 1984). Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 18, DOI:10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008